Editorial (diségno, 2021)
In the Drawing of Architecture, a large part of the production is devoted to reasonings on dreamed architectures, sketches and visions that open the door of the unconscious and desire. This is a Visionary Drawing that the editor of this issue, Paolo Belardi, has chosen to propose according to an expositive thread leading from the interpretation of a desired reality, to a dreamed hallucination of the consciousness or of perception. [read more]